THE 21ST CENTURY SKILLS ON CHEMISTRY LEARNING BASED ON VIRTUAL LAB IN SENIOR HIGH SCHOOL - Anita Setiawati; Devira Nur Ajizah; Nela Nur Anisa; Pristiningtyas Ambarwati; Zakiyah Ayu Noor Izzati; Farah Erika (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
Research aims to review 21st century skills in-based senior high school chemistry learning virtual labs. The components that will be studied include: (1) Barriers to high school chemistry learning; (2) 21st century skills; (3) The advantages and disadvantages of using virtual labs; and (4)implications of virtual labs on 21st century skills. The method used in writing the article is descriptive, qualitative by analyzing national and international articles related to 21st century skills in-based high school chemistry learning virtual labs. The results show that high school chemistry learning uses virtual The lab can integrate 21st century skills, visualize abstract concepts into concrete, support student-centered learning, reduce anxiety in facing real laboratories, and increase students' self-efficacy so that they can become a capable supporting unit for the chemistry learning process. However, in its implementation it needs to be adapted to content and activities that refer to various aspects of 21st century skills.